Routine health surveillance data: a 21-year quantitative cross-sectional study of first-time opioid addiction treatment among older adults - CAREW, ANNE MARIE (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2019)
Introduction: Current literature identifies older people who use opioids as a neglected population. Little is known about temporal changes, treatment demand or treatment discharge outcomes among this population. Aim: This thesis aims to investigate the age profile of the opioid treatment population over a twenty-one-year-period (1995-2015) using national cross-sectional health surveillance data following an EU wide protocol, and to explore typologies of client characteristics, behaviours and associated treatment discharge outcomes. Methods: A systematic literature review was carried out to establish what was known about ageing among people treated for opioid use and outcomes of that treatment. Observational data from the EU Treatment Demand Indicator (TDI) for Ireland (1995-2015) was analysed for trends in new opioid treatment admissions, ageing and drug-using behaviours. Trends in age-adjusted treatment admission rates were examined using Joinpoint regression analysis. The typology of opioid-using behaviours and client characteristics was examined using a cluster analysis for similar groups. Treatment duration and completion rates were analysed overall, and by treatment modality utilising survival analysis methods. Results: Data from 20,698 individuals entering treatment in Ireland for the first time showed that while the trend of age-adjusted incidence declined between 1995 and 2015, incidence among older age groups increased, with a rising incidence not previously observed among those aged 45 years and older. The profile of people entering treatment for the first time has changed. Age entering treatment and duration of opioid use prior to treatment has increased significantly, and subgroups of early and late treatment entries, and early and late opioid onset were observed. Five distinct profiles, or subgroups were detected with type of opioid and age of opioid use onset as distinguishing features. There was evidence of important temporal changes within subgroups, including (1) significant changes in the median age entering treatment, and (2) significant changes in opioid-using durations prior to seeking treatment. Only three of the five groups contributed to the overall temporal shift in ageing among the opioid treatment population. Furthermore, there was no evidence that ageing trends were driven by over-the-counter or prescription opioid users. It is proposed that 'older' is defined as 35 years of age or older when entering treatment, or, if younger than 35 years, where there has been prolonged opioid use for 10 or more years. The investigation of treatment completion rates for opioid treatment entrants revealed that regardless of treatment modality, rates of opioid treatment dropout were high with few successfully completing treatment. A total of ten risk and protective factors were associated with treatment retention. The ten factors reflect three categories; sociodemographic factors (age, remaining in school until at least 16 years of age, employment status and location of residence), pre-treatment drug use factors (frequency of opioid use in the month prior to treatment, route of opioid administration, and injecting status at treatment entry) and treatment factors (treatment setting, year commenced treatment and referral source), which varied by treatment modality, demonstrating that key indicators of treatment compliance are not uniform across treatment modality. There was considerable variation not only in treatment exposure across modality, but also in the characteristics which may be associated with treatment retention. Older age at treatment entry was associated with reduced risk of treatment dropout in certain circumstances. Conclusion: Current knowledge about the ageing cohort of opioid users is limited by the failure to recognise the value of existing health surveillance data and the absence of a universally accepted, evidence based definition of older among people who use drugs. The study highlights the importance of utilising national datasets to identify hidden groups at risk of chronic harm and dispels the belief that data is the greatest limitation to understanding illicit substance use among older adults. The study finds that the opioid treatment population is ageing; those entering treatment are older, are injecting longer and taking longer to enter treatment. Trends are driven by population subgroups. Several characteristics including age are associated with duration of treatment retention and treatment completion. It is important to adequately understand the specific needs of the ageing population who use opioid drugs in order to deliver appropriate care.
APPROVED
Keywords: Ageing; Opioid; Treatment; Addiction; National Drug Treatment Reporting System; NDTRS; Ireland; Older; Heroin